Perioperative Anemia, Gender, Blood Transfusion and Urine Output during Cardiopulmonary Bypass: Risk Factors for Acute K. Injury - Asma Hassan, Attaullah Younas, Ajwad Farogh, Naseem Ahmed, Tariq Bashir, Sadaf Iftikhar, Shamila Afshan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of current study was to find out the factors causing Acute Kidney Injury (AKI) in the postoperative period of cardiac surgery. This prospective study, Peri-operative Anemia, Urine Output, gender, need for Intra-operative blood transfusion were analyzed for association of AKI. Material and Method: The study was conducted at Cardiac Center, QAMC Bahawalpur from January, 2019 to June, 2021. A total of 180 patients who underwent cardiopulmonary bypass for IHD and Valve surgery were studied. CPB hemoglobin levels, Blood Transfusion in OR, Gender specificity, Peri-operative urine output (Group1 UO <4ml/kg/hr: Group 2 UO > 4ml/kg/hr) were correlated to establish their relationship in causing post-operative Acute Kidney Injury. The patients were divided into two groups one who had Acute Kidney Injury other who don’t. Results: Acute kidney injury developed in 20 out of 180 patients, current study showed insignificant relation between CPB time, X clamp time, Gender, Surgery type, MAP and Postoperative Acute Kidney Injury. Acute Kidney Injury was more associated with diabetes, need of blood transfusion, perioperative hemofiltration and reduced urine output. Conclusion: Current study showed that Acute Kidney injury is an avoidable complication if hemoglobin levels are kept above 8-9 gm/dl to ensure proper oxygen supply and need of Intraoperative hemofiltration and BT is reduced by reducing circuit length thus hemodilution and found a urine output less than 4 ml/kg/hr during cardiopulmonary bypass carries major risk for AKI.